Comparison of prescription patterns of antihypertensives in the geriatric population with JNC 8 guidelines - Kousalya Prabahar (Journal of Applied Pharmaceutical Science, 2021)
In the management of hypertensive patients, variations in the treatment from the standard guidelines could be observed. Irrationality in the prescribing pattern may cause serious health issues, as well as increased treatment cost. The objective of the study was to assess the current prescribing patterns of antihypertensives in the geriatric population and to compare the prescription pattern with the standard treatment guidelines of the Joint National Committee (JNC 8). A prospective observational study was conducted in a general medicine unit of a tertiary care hospital for a period of 5 months, using a structured proforma. Four hundred cases were collected. As per JNC 8, calcium channel blockers (88%) were found to be most commonly prescribed, which was in accordance with the JNC 8 treatment algorithm. The second most commonly prescribed drug was beta blockers (BBs) in our study, but BBs were not a preferred therapy according to the guidelines. With regard to comorbidities, according to the JNC 8 guidelines, the treatment of choice for diabetes was angiotensin-converting enzyme inhibitors/angiotensin-receptor blockers, calcium channel blockers (CCBs), and diuretics. But in our study, CCBs, BBs, and diuretics were given. There was 27.5% deviation from the JNC 8 guidelines. Optimizing the treatment pattern in accordance with standard treatment guidelines will decrease the risk of complications.
Keywords: Hypertension, prescription pattern, JNC 8, geriatrics